Metal-air battery

The metal-air battery employs a lattice-like spacer with through-holes to address resistance and shape change issues, ensuring stable electrolyte movement and improved performance.

JP7602404B2Active Publication Date: 2024-12-18SHARP KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021038911
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-11
Publication Date
2024-12-18
Estimated Expiration
2041-03-11

AI Technical Summary

Technical Problem

Conventional metal-air batteries face issues with increased resistance due to complex electrolyte paths and inability to suppress negative electrode shape changes during charge/discharge reactions, particularly when using porous materials or nonwoven fabrics as spacers.

Method used

A metal-air battery design featuring a lattice-like spacer with through-holes and varying lattice spacings, allowing for smooth electrolyte movement and suppressing negative electrode shape changes by applying uniform pressure.

Benefits of technology

The design enhances electrolyte space utilization, reduces internal resistance, and improves battery performance by maintaining electrode shape stability and promoting efficient ion movement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602404000001
    Figure 0007602404000001
  • Figure 0007602404000002
    Figure 0007602404000002
  • Figure 0007602404000003
    Figure 0007602404000003
Patent Text Reader

Abstract

To provide a metal-air battery capable of suppressing shape change of a negative electrode while securing an electrolyte space.SOLUTION: A metal-air battery 1 includes a metal negative electrode 4, an air electrode 5, and a spacer 10 arranged between the metal negative electrode 4 and the positive electrode 5. The spacer 10 is composed of a grid-like framework extending in three dimensions and an electrolytic solution 9 filling the space between the frameworks.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal-air battery comprising a metallic negative electrode and a metallic positive electrode. [Background technology]

[0002] In conventional metal-air batteries, a spacer was sometimes placed between the negative electrode and the charging electrode, or between the negative electrode and the air electrode, in order to retain the electrolyte in the reaction space and improve battery performance (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-224383 A [Patent Document 2] JP 2020-126754 A Summary of the Invention [Problem to be solved by the invention]

[0004] The metal-air battery described in Patent Document 1 includes a negative electrode, an ion migration layer, and a positive electrode separated from the negative electrode via the ion migration layer. In this metal-air battery, a spacer may be inserted to maintain the shape of the assembly consisting of the ion migration layer and the negative electrode, and a porous material is cited as a material for the spacer.

[0005] The air secondary battery described in Patent Document 2 includes an electrode group including an air electrode and a negative electrode stacked with a separator interposed therebetween, and a container that contains the electrode group together with an alkaline electrolyte. A nonwoven fabric made of polyamide fiber is cited as a material used for the separator.

[0006] In the above-mentioned metal-air battery, a porous material or nonwoven fabric is used as a spacer, but the path through which the electrolyte passes is complicated, which poses the problem of increased resistance.

[0007] However, when charge and discharge reactions are repeated, the reactive active material expands, which can cause the negative electrode to deform. Some spacers have a hollow center, which corresponds to the position of the reaction field, and this type of spacer has the problem of being unable to prevent shape changes in the negative electrode.

[0008] The present invention has been made to solve the above problems, and has an object to provide a metal-air battery that can suppress deformation of the negative electrode while ensuring space for an electrolyte. [Means for solving the problem]

[0009] The metal-air battery of the present invention is a metal-air battery comprising a metal negative electrode, a positive electrode, and a spacer disposed between the metal negative electrode and the positive electrode, and is characterized in that the spacer is composed of a lattice-shaped skeleton stretched in three dimensional directions, and an electrolyte solution filling the spaces between the skeleton.

[0010] In the metal-air battery according to the present invention, the spacer may have a through-hole that penetrates the spacer in a thickness direction in which the metal negative electrode and the positive electrode face each other.

[0011] In the metal-air battery according to the present invention, the through-holes may be configured so that their size varies in the thickness direction.

[0012] In the metal-air battery according to the present invention, the size of the through-hole may be smaller on the metal negative electrode side and larger on the positive electrode side.

[0013] In the metal-air battery according to the present invention, the spacer may be configured to be composed of a first skeleton and a second skeleton having lattice spacings different from each other, and the lattice spacing of the first skeleton may be an integer multiple of 2 or more of the lattice spacing of the second skeleton.

[0014] In the metal-air battery according to the present invention, the skeleton may be configured to be arranged with periodicity in a planar direction along a surface in contact with the metal negative electrode and in the thickness direction.

[0015] In the metal-air battery according to the present invention, the skeleton may have a thickness of 0.5 to 2 mm.

[0016] In the metal-air battery according to the present invention, the volume of the vesicles partitioned by the skeleton is 30 to 100 mm 3 The configuration may be as follows.

[0017] In the metal-air battery according to the present invention, the spacer may have a thickness of 1.5 to 5 mm.

[0018] In the metal-air battery according to the present invention, the metal negative electrode may have a thickness of 1 mm or more, and the spacer may have a thickness of 0.75 times or more the thickness of the metal negative electrode.

[0019] In the metal-air battery according to the present invention, a separator is provided between the metal negative electrode and the spacer, The ratio of the thickness of the separator to the lattice spacing of the skeleton may be in the range of 0.05 to 0.09.

[0020] In the metal-air battery according to the present invention, the metal-air battery may be configured such that a surface facing the metal negative electrode is clamped by a pair of fasteners. Effect of the Invention

[0021] According to the present invention, by providing a spacer, it is possible to suppress shape change due to a reaction of the metal negative electrode, while ensuring a space for the electrolyte so that substances can move smoothly inside. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a metal-air battery according to a first embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing a conventional metal-air battery. [Diagram 3] FIG. 1 is a schematic front view showing a spacer in a metal-air battery according to a first embodiment of the present invention. [Figure 4] FIG. 11 is a schematic front view showing a spacer in Modification 1. [Diagram 5] FIG. 11 is a schematic front view showing a spacer in Modification 2. [Figure 6] FIG. 13 is a schematic front view showing a spacer in Modification 3. [Figure 7A] FIG. 11 is a schematic front view showing a spacer according to a second embodiment of the present invention. [Figure 7B] FIG. 7B is a schematic cross-sectional view of the spacer shown in FIG. 7A. [Figure 8] 1 is a characteristic chart showing the results of Experiment 1. [Figure 9] 13 is a characteristic chart showing the results of Experiment 2. [Figure 10] 13 is a characteristic chart showing the results of Experiment 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] (First embodiment) Hereinafter, a metal-air battery according to a first embodiment of the present invention will be described with reference to the drawings.

[0024] FIG. 1 is a schematic cross-sectional view showing a metal-air battery according to a first embodiment of the present invention.

[0025] The metal-air battery 1 according to the first embodiment of the present invention is a three-electrode metal-air secondary battery having a structure in which a metal negative electrode 4 is sandwiched between a charging electrode 3 and an air electrode 5 (positive electrode). Examples of the metal-air battery 1 include a zinc-air battery, a lithium-air battery, a sodium-air battery, a calcium-air battery, a magnesium-air battery, an aluminum-air battery, and an iron-air battery. The metal-air battery 1 is filled with an electrolyte 9 and is enclosed in a packaging material 2 to maintain its hermeticity.

[0026] The charging electrode 3 and the air electrode 5 face the inner surface of the packaging material 2 via a water-repellent film 6, and the packaging material 2 has openings at locations corresponding to the charging electrode 3 and the air electrode 5, allowing only air to pass through.

[0027] The air electrode 5 is a porous electrode having an air electrode catalyst and serving as a discharge positive electrode. When an alkaline aqueous solution is used as the electrolyte in the air electrode 5, a discharge reaction occurs on the air electrode catalyst in which water supplied from the electrolyte or the like reacts with oxygen gas supplied from the atmosphere and electrons to generate hydroxide ions.

[0028] The charging electrode 3 is a porous electrode made of an electronically conductive material. When an alkaline aqueous solution is used as the electrolyte, a charging reaction occurs in the charging electrode 3, in which oxygen, water, and electrons are produced from hydroxide ions.

[0029] The metal negative electrode 4 is covered by a separator 7 on the surface facing the charging electrode 3 and the surface facing the air electrode 5. The metal negative electrode 4 and the separator 7 are also covered by a PE bag 8 (polyethylene bag), and the PE bag 8 has an opening.

[0030] A spacer 10 is disposed between the metal anode 4 and the air cathode 5. The spacer 10 is composed of a lattice-shaped skeleton 11 stretched in a three-dimensional direction and an electrolyte that fills the gaps between the skeleton 11. The detailed shape of the skeleton 11 will be described with reference to FIG. 3 described later. The spacer 10 is preferably a material that does not react with the electrolyte of the battery. When the electrolyte is a strong alkaline electrolyte, the spacer 10 is made of a resin that is resistant to alkali, and specific examples of the resin include polyethylene, polypropylene, ABS resin, and PTFE resin. If the anode and cathode are in contact with the metal spacer 10, electricity will flow inside the battery, causing a short circuit, so metals are not included.

[0031] The metal-air battery 1 may have a surface facing the metal negative electrode 4 sandwiched between a pair of fasteners 20. Even if pressure is suppressed by the spacer 10, the pressure generated by the shape change of the metal negative electrode 4 is pushed back to the opposite side, causing the battery to expand. Therefore, by sandwiching the battery with the fasteners 20, the expansion of the battery itself can be suppressed.

[0032] Next, for comparison with the metal-air battery 1 according to the first embodiment of the present invention, a conventional metal-air battery will be described with reference to FIG.

[0033] FIG. 2 is a schematic cross-sectional view showing a conventional metal-air battery.

[0034] In the conventional metal-air battery (conventional battery 100), a frame-type support 110 is provided instead of the spacer 10 in the first embodiment. This frame-type support 110 exists only on the outer periphery on the surface facing the metal negative electrode 4 and the air electrode 5, and a space for passing the electrolyte 9 is provided in the open center. In the metal-air battery, the metal negative electrode 4 may expand and change in shape due to a reaction. At this time, since the center of the frame-type support 110 is hollow on the surface facing the metal negative electrode 4, the shape change of the metal negative electrode 4 cannot be suppressed, and as shown in FIG. 2, a part of the metal negative electrode 4 expands so as to enter the cavity of the frame-type support 110. As a result, the electrolyte space becomes narrower and the distance to the air electrode 5 changes, resulting in a decrease in battery performance.

[0035] In contrast, in the present embodiment, a spacer 10 having a lattice-like skeleton 11 is used to suppress shape change due to reaction of the metal negative electrode 4. Next, a detailed structure of the spacer 10 in the present embodiment will be described with reference to FIG.

[0036] FIG. 3 is a schematic front view showing a spacer in the metal-air battery according to the first embodiment of the present invention.

[0037] FIG. 3 shows the state of the spacer 10 (first spacer 10a) in a state of being in contact with the metal negative electrode 4. On the surface in contact with the metal negative electrode 4, a plurality of skeletons 11 arranged in the vertical and horizontal directions at a predetermined interval form through holes 12. In this embodiment, the through holes 12 are formed so as to be square when viewed from the side of the metal negative electrode 4. In FIG. 3, the spacer 10 is shown in a schematic manner, and the number of skeletons 11 and through holes 12 is omitted, but in an actual structure, the number of skeletons 11 and through holes 12 may be appropriately adjusted according to the size of the spacer 10. In addition, in the spacer 10, as shown in FIG. 1, the skeletons 11 are arranged at intervals in the thickness direction in which the metal negative electrode 4 and the air electrode 5 face each other. In this way, by providing the spacer 10, it is possible to secure an electrolyte space so that a substance can move smoothly inside while suppressing a shape change due to a reaction of the metal negative electrode 4. In addition, by providing a through hole 12 that penetrates the spacer 10 in the thickness direction where the metal negative electrode 4 and the air electrode 5 face each other, the path through which the electrolyte 9 passes is not complicated, and the movement of materials in the thickness direction is smooth, thereby promoting the battery reaction.

[0038] As described above, the skeleton 11 is arranged with periodicity in the planar direction and thickness direction along the surface in contact with the metal negative electrode 4. By forming the skeleton 11 in a periodic pattern in this way, it is possible to apply uniform pressure to the surface of the metal negative electrode 4 in contact with the spacer 10, so that pressing can be performed evenly and shape change can be further suppressed.

[0039] The deterioration of the battery performance can be more effectively suppressed by appropriately setting various parameters of the spacer 10, such as the thickness of the spacer itself, the width of the skeleton 11, and the size of the through-holes 12. The results of an experiment examining the various parameters of the spacer 10 will be described later with reference to Figs. 8 to 10.

[0040] Next, modified examples 1 and 2 in which the shape of through-hole 12 is different will be described with reference to FIGS.

[0041] FIG. 4 is a schematic front view showing a spacer in the first modification.

[0042] In the first modification (second spacer 10b), the through holes 12 are formed to have a hexagonal shape when viewed from the side of the metal negative electrode 4. In other words, a honeycomb structure is formed by combining a plurality of hexagonal through holes 12.

[0043] FIG. 5 is a schematic front view showing a spacer in the second modification.

[0044] In the second modification (third spacer 10c), the through-holes 12 are formed to be diamond-shaped when viewed from the side of the metal negative electrode 4. That is, the skeletons 11 are tilted with respect to the perpendicular line of the contact surface with the electrode, and the linearly extending skeletons 11 are arranged to intersect with each other, thereby forming the diamond-shaped through-holes 12.

[0045] Next, a third modification in which a frame is provided on the periphery will be described with reference to FIG.

[0046] FIG. 6 is a schematic front view showing a spacer in the third modification.

[0047] In the third modification (fourth spacer 10d), a frame 13 is provided on the periphery. In this way, the frame 13 is provided to strongly reinforce the periphery, while the central skeleton is formed of the skeleton 11, providing a gap to ensure space for the electrolyte. The frame 13 serves to protect the central skeleton from physical impacts applied from outside the battery.

[0048] Second embodiment Next, a second embodiment in which through holes 12 of different sizes are provided will be described with reference to FIG.

[0049] FIG. 7A is a schematic front view showing a spacer in a second embodiment of the present invention, and FIG. 7B is a schematic cross-sectional view of the spacer shown in FIG. 7A.

[0050] In the second embodiment, two types of skeletons 11 (first skeleton 11a and second skeleton 11b) are provided, and the sizes of the through-holes 12 are different between the metal negative electrode 4 side and the air electrode 5 side. In FIG. 7A, in order to distinguish between the first skeleton 11a and the second skeleton 11b, the first skeleton 11a is shown by a solid line, and the second skeleton 11b is shown by a dashed line. In this embodiment, the through-holes 12 are formed by the first skeleton 11a and the second skeleton 11b on the metal negative electrode 4 side (left side in FIG. 7B), and the through-holes 12 are formed only by the first skeleton 11a on the air electrode 5 side (right side in FIG. 7B). The first skeleton 11a forms a through-hole 12 with a large size, and the second skeleton 11b is located between the adjacent first skeletons 11a. The lattice spacing of the first skeletons 11a is arranged to be an integer multiple of the lattice spacing of the second skeleton 11b by 2 or more. That is, the second skeleton 11b divides the through-hole 12 formed by the first skeleton 11a into a plurality of through-holes 12 having smaller sizes. When the spacer 10 is viewed from the metal negative electrode 4 side, the first skeleton 11a overlaps on the metal negative electrode 4 side and the air electrode 5 side, thereby reducing the loss of porosity.

[0051] The spacer 10 is not limited to the above-mentioned configuration, and the size of the through-holes 12 may be changed by changing the interval between the skeletons 11 depending on the position in the thickness direction. Specifically, on the metal negative electrode 4 side, the skeletons 11 are densely arranged to reduce the size of the through-holes 12, and on the air electrode 5 side, the skeletons 11 are sparsely arranged to increase the size of the through-holes 12. In this way, various characteristics can be obtained by changing the size of the through-holes 12. For example, by making the through-holes 12 smaller, a dense structure can be obtained to withstand pressure due to shape change, and by making the through-holes 12 larger, the electrolyte space can be increased, and the movement of substances can be promoted.

[0052] In this embodiment, because a shape change occurs on the negative electrode side, it is desirable to reduce the size of the through holes 12 on the negative electrode side in order to suppress expansion in the compartments within the skeleton 11. However, if the size of the through holes 12 is reduced throughout the entire thickness of the spacer 10, the area occupied by the skeleton 11 in a cross section perpendicular to the thickness direction increases, resulting in a decrease in the aperture ratio and an impairment of material transfer within the spacer 10. Therefore, it is desirable to increase the size of the through holes 12 on the air electrode 5 side.

[0053] (Experimental Results) In the experiment of the metal-air battery 1 according to the present invention, a zinc-air battery, which is a kind of the metal-air battery 1, was produced. The metal negative electrode 4 of the zinc-air battery was formed of ZnO, and 7.5 Ah was supported on a metal current collector. An alkaline aqueous solution was used for the electrolyte 9. The area of ​​the water-repellent film 6 was 7×7 cm, the reaction surface of the charging electrode 3 was 7×7 cm, the anion film was 9×7 cm, the reaction surface of the metal negative electrode 4 was 7×7 cm, the opening of the negative electrode case (PE bag 8) was 6.5×6.5 cm, and the reaction surface of the air electrode 5 was 6.5×6.5 cm. The spacer 10 was made of resin, had an overall surface of 7×7 cm, a thickness of 3 mm, a width of the skeleton 11 of 0.5 mm, and each lattice pattern was a square of 4×4 mm. In other words, the size of one lattice pattern corresponds to one through hole 12. The above-mentioned charging electrode 3, metal negative electrode 4, spacer 10, and air electrode 5 were laminated in this order, and the packaging material 2 was heat-sealed to prepare an example of the metal-air battery 1.

[0054] In addition to the above-mentioned embodiment, a comparative example was prepared in which a nonwoven paper fabric of the same thickness was used instead of the spacer 10, and charge / discharge measurements were carried out for data comparison.

[0055] The measurement conditions for the charge / discharge measurements were a current density of 10 mA / cm 2 The charge-discharge cycle was repeated several times, with one charge and one discharge being one set, and the current density of the discharge was 60mA / cm. 2 It was decided.

[0056] In the embodiment, 60 mA / cm 2 The voltage at the reference sample was 1.02 V, whereas the voltage at the reference sample was 60 mA / cm 2 The voltage at 60 mA / cm was 0.97 V. Therefore, by providing the spacer 10 to the metal-air battery 1, 2 An improvement of 0.05V was confirmed in the voltage at

[0057] In the comparative example, the current was 60 mA / cm in the eighth charge / discharge cycle. 2 In the example, the discharge capacity at the first charge / discharge cycle was less than 1% of the initial discharge capacity, whereas in the example, 14 or more charge / discharge cycles were performed. This is because the spacer 10 in the example ensured a space for the electrolyte, and thus did not inhibit the mass transfer of ions.

[0058] (Experiment 1) Next, the results of experiment 1, in which the thickness of the skeleton 11 was compared, will be described with reference to FIG.

[0059] FIG. 8 is a characteristic chart showing the results of Experiment 1.

[0060] In Experiment 1, Experimental Examples 1 to 5 were produced in which the thickness of the skeleton 11 was different. Specifically, in Experimental Example 1, the thickness of the skeleton 11 was 0.4 mm, in Experimental Example 2, the thickness of the skeleton 11 was 0.5 mm, in Experimental Example 3, the thickness of the skeleton 11 was 1 mm, in Experimental Example 4, the thickness of the skeleton 11 was 2 mm, and in Experimental Example 5, the thickness of the skeleton 11 was 2.1 mm. Note that, in Experimental Examples 1 to 5, the parameters other than the thickness of the skeleton 11 are common to the above-mentioned examples.

[0061] In experiment 1, the initial discharge voltage, the number of charge / discharge cycles, breakage during assembly, and porosity were evaluated. The thicker the skeleton 11, the smaller the porosity of the spacer 10 seen from the surface in contact with each electrode, making it more difficult for ions to pass through the electrolyte space inside the spacer 10, increasing the internal resistance of the battery and resulting in a smaller discharge voltage. If the skeleton 11 is too thin, the physical strength of the spacer 10 itself is insufficient, causing breakage during battery assembly. The criterion for ending the charge / discharge cycle is that the discharge voltage can no longer reach a specified value (0.8V) or more. Since the discharge voltage decreases with each cycle, the lower the initial discharge voltage, the fewer the number of charge / discharge cycles.

[0062] In Experimental Example 1, the porosity was large, but since it was broken during assembly, other items could not be evaluated. In Experimental Example 5, the porosity was small and the initial discharge voltage was low, so the number of charge / discharge cycles was one. According to the results of Experiment 1, the skeleton 11 preferably has a thickness of 0.5 to 2 mm.

[0063] (Experiment 2) Next, the results of Experiment 2, which compared the volume of vesicles, will be described with reference to FIG.

[0064] FIG. 9 is a characteristic chart showing the results of Experiment 2.

[0065] In Experiment 2, Experimental Examples 6 to 10 were prepared, each of which had a different vesicle volume. The volume of the vesicle was determined by the size of the through-holes 12 and the spacing of the skeleton 11 in the thickness direction. Specifically, in Experimental Example 6, the volume of the vesicle was 20 mm 3 In Experimental Example 7, the volume of the vesicle was 30 mm 3 In Experimental Example 8, the volume of the vesicle was 50 mm 3 In Experimental Example 9, the volume of the vesicle is 100 mm 3 In Example 10, the volume of the vesicle was 150 mm 3 In Experimental Examples 6 to 10, parameters other than the volume of the vesicles are common to the above-mentioned examples.

[0066] In experiment 2, the mAh at the second cycle, the number of charge / discharge cycles, the porosity, and the ratio of the thickness of the separator 7 to the lattice spacing were evaluated. In the spacer 10, the relative porosity is determined by the volume of the vesicles, which determines the ratio of the thickness of the separator 7 to the lattice spacing. When the volume of the vesicles is reduced, the pattern becomes denser, and the porosity of the spacer 10 is reduced. This makes it difficult for ions to pass through the electrolyte space in the spacer 10, increasing the internal resistance of the battery and resulting in a smaller discharge voltage. When the volume of the vesicles is increased, the effect of pressing the reaction surface evenly is reduced, allowing the expansion of the metal anode 4 within the voids of the skeleton 11, thereby reducing the number of charge / discharge cycles.

[0067] In Experimental Examples 6 and 10, the mAh at the second cycle was 300, which was lower than that of Experimental Examples 7 to 9. Furthermore, Experimental Examples 6 and 10 had two cycles, which was less than that of the other Experimental Examples. Combined with the mAh at the second cycle, it can be determined that recharging is difficult. According to the results of Experiment 2, the volume of the vesicles partitioned by the skeleton 11 is 30 to 100 mm 3 In addition, the ratio of the thickness of the separator 7 to the lattice spacing of the skeleton 11 is preferably 0.05 to 0.09.

[0068] (Experiment 3) Next, the results of Experiment 3, which compared the thickness of the spacer 10, will be described with reference to FIG.

[0069] FIG. 10 is a characteristic chart showing the results of Experiment 3.

[0070] In Experiment 3, Experimental Examples 11 to 15 were produced in which the spacer 10 had different thicknesses. Specifically, in Experimental Example 11, the spacer 10 had a thickness of 1 mm, in Experimental Example 12, the spacer 10 had a thickness of 1.5 mm, in Experimental Example 13, the spacer 10 had a thickness of 3 mm, in Experimental Example 14, the spacer 10 had a thickness of 5 mm, and in Experimental Example 15, the spacer 10 had a thickness of 6 mm. Note that in Experimental Examples 11 to 15, the parameters other than the thickness of the spacer 10 are common to the above-mentioned examples.

[0071] In experiment 3, the thickness ratio between the spacer 10 and the metal negative electrode 4, the Coulombic efficiency, and the energy density were evaluated. The Coulombic efficiency is the ratio of the electrical capacity (Ah) fed into the battery during charging to the electrical capacity (Ah) discharged by the battery during discharging. The energy density is the ratio of the total amount of energy (Wh) stored in the battery to the weight (kg) of the battery itself. The thickness ratio between the spacer 10 and the metal negative electrode 4 was calculated assuming that the thickness of the metal negative electrode 4 was 2 mm, and the energy density was a calculated value calculated from the thickness ratio between the spacer 10 and the metal negative electrode 4.

[0072] The spacer width (thickness of the spacer 10) is proportional to the volume of the electrolyte 9 present between the negative and positive electrodes, and the larger the spacer width, the higher the weight of the battery, and the lower the energy density. Discharge of the metal-air battery 1 occurs by a chemical reaction, and the concentration of reactants and products changes due to discharge. This change in concentration causes a decrease in battery performance, such as polarization (voltage drop). Here, the larger the volume of the electrolyte 9 present between the negative and positive electrodes, the more the concentration change during discharge can be alleviated, so the voltage drop is suppressed and the dischargeable capacity increases. That is, the Coulomb efficiency, which is proportional to the discharge capacity, also increases. In addition, the thickness of the metal negative electrode 4 is proportional to the amount of the negative electrode active material, and the smaller the thickness of the metal negative electrode 4, the lower the weight ratio of the negative electrode active material in the battery, and the lower the energy density. That is, the larger the thickness of the metal negative electrode 4, the more desirable it is, and it is preferably 1 mm or more.

[0073] In Experimental Examples 12 to 15, the Coulombic efficiency was about 80%, while in Experimental Example 11, the Coulombic efficiency was 17%, which was clearly small. In addition, in Experimental Examples 11 to 14, the energy density was 100 Wh / kg or more, while in Experimental Example 15, the energy density was 97 Wh / kg, which was lower than the predetermined value (100 Wh / kg). According to the results of Experiment 3, the thickness of the spacer 10 is 1.5 mm or more and 5 mm or less, and the thickness of the spacer 10 is preferably 0.75 times or more the thickness of the metal negative electrode 4.

[0074] It should be noted that the embodiments disclosed herein are illustrative in all respects and are not intended to provide a basis for a restrictive interpretation. Therefore, the technical scope of the present invention is not interpreted solely by the above-described embodiments, but is defined by the claims. Furthermore, all modifications within the scope and meaning equivalent to the claims are included. [Explanation of symbols]

[0075] 1. Metal-air battery 2 Packaging material 3 charging pole 4 Metallic anode 5 Air pole 6 Water-repellent film 7 Separator 8 PE bags 9 Electrolyte 10 Spacer 11 Skeleton 12 Through hole 20 Fixtures

Claims

1. A metal-air battery comprising a metal negative electrode, a positive electrode, and a spacer disposed between the metal negative electrode and the positive electrode, the spacer is composed of a lattice-shaped skeleton stretched in a three-dimensional direction and an electrolyte filling the spaces between the skeletons, and has through-holes passing through the spacer in a thickness direction in which the metal negative electrode and the positive electrode face each other; The size of the through holes varies in the thickness direction, being smaller on the metal negative electrode side and larger on the positive electrode side. A metal-air battery characterized by:

2. The metal-air battery according to claim 1, the spacer is composed of a first skeleton and a second skeleton having different lattice spacings, The lattice spacing of the first skeleton is an integer multiple of 2 or more of the lattice spacing of the second skeleton. A metal-air battery characterized by:

3. The metal-air battery according to claim 1 or 2, The skeleton is arranged with periodicity in a plane direction along the surface in contact with the metal negative electrode and in the thickness direction. A metal-air battery characterized by:

4. A metal-air battery according to any one of claims 1 to 3, The skeleton has a thickness of 0.5 to 2 mm. A metal-air battery characterized by:

5. A metal-air battery according to any one of claims 1 to 4, The volume of the vesicle defined by the skeleton is 30 to 100 mm 3 To be A metal-air battery characterized by:

6. A metal-air battery according to any one of claims 1 to 5, The thickness of the spacer is 1.5 to 5 mm. A metal-air battery characterized by:

7. A metal-air battery according to any one of claims 1 to 6, The thickness of the metal negative electrode is 1 mm or more, The thickness of the spacer is 0.75 times or more the thickness of the metal negative electrode. A metal-air battery characterized by:

8. A metal-air battery according to any one of claims 1 to 7, a separator is provided between the metal negative electrode and the spacer; The ratio of the thickness of the separator to the lattice spacing of the skeleton is 0.05 to 0.

09. A metal-air battery characterized by:

9. A metal-air battery according to any one of claims 1 to 8, The metal-air battery has a surface facing the metal negative electrode sandwiched between a pair of fasteners. A metal-air battery characterized by:

10. A metal-air battery comprising a metal negative electrode, a positive electrode, and a spacer disposed between the metal negative electrode and the positive electrode, the spacer is composed of a lattice-shaped skeleton stretched in a three-dimensional direction and an electrolyte filling the spaces between the skeletons; the skeleton of the spacer is composed of a first skeleton and a second skeleton having different lattice spacings, The lattice spacing of the first skeleton is an integer multiple of 2 or more of the lattice spacing of the second skeleton. A metal-air battery characterized by:

11. A metal-air battery comprising a metal negative electrode, a positive electrode, and a spacer disposed between the metal negative electrode and the positive electrode, the spacer is composed of a lattice-shaped skeleton stretched in a three-dimensional direction and an electrolyte filling the spaces between the skeletons; The skeleton is arranged with periodicity in a plane direction along a surface in contact with the metal negative electrode and in a thickness direction in which the metal negative electrode and the positive electrode face each other. A metal-air battery characterized by:

Citation Information

Patent Citations

  • JP1975003026U

  • JP1978063521U

  • electrochemical power generator

    JP1996505730A

  • Novel separator for electrochemical systems

    JP2014528139A

  • Air battery and air battery stack

    JP2015041499A